Development of Deaf Students Batik Skills - Megarani Rosnadia; Abdul Huda; Ahsan Romadlon Junaidi (Department of Special Education, 2020)
Deaf is someone who has a hearing loss, which causes hearing impairment to experience limitations in language, communication, and capturing information. With all the limitations experienced and the potential it has, the deaf child needs to be equipped with life skills and one of them is the skill of making batik. Research Objectives to: 1) describe the process of planning a batik skills training program; 2) describe the strategy of implementing batik skills coaching, and 3) describe the evaluation methods for developing batik skills of deaf students in Blitar City. This study uses a qualitative approach to the type of case study research. The study was conducted at SLB in Blitar City. Data was collected through interviews and observations, and analyzed using content analysis. The results of this study indicate that: The process of planning a batik skills training program is held in a meeting that discusses the identification of field needs and formulating learning objectives which are then compiled in a lesson plan that is aligned with K13; The strategy of developing batik skills in collaboration with batik artisans in Pakunden, the Wali Murid Circle of Friends, and the implementation of classes; The results of the work of developing batik skills are evaluated through the provision of appreciation in the form of participation in bazaars, exhibitions, competitions and also used as a uniform as a school identity. In this way, the interests of deaf children develop their skills.